The Activity of Wungu Leaf (Graptophyllum pictum (L) Griff) Extract in Reducing Blood Glucose Level of Hyperglycemic Mice - Hayatul Rahmi; I Made Artika; Norman Razief Azwar; Djarot Sasongko Hami Seno; Waras Nurcholis (Current Biochemistry, 2014)
Wungu leaf (Graptophyllum pictum (L.) Griff) is a plant thought to have potential use in alleviating symptoms of diabetes mellitus. The purpose of the present study was to evaluate the activity of wungu leaf extracts in decreasing blood glucose level of alloxan (200 mg/kg BW)-induced hyperglycemic mice. Extracts of wungu leaf were obtained by macerating with ethanol and then partitioning the extract with diethyl ether, ethyl acetate, and butanol. Each extract obtained was used to treat hyperglycemic mice for 28 days. The results showed that wungu leaf extracts have the ability to decrease the blood glucose level of hyperglycemic mice (dose 50 mg/kg BW). The ethyl acetate extract showed the highest activity, bringing about a decrease of blood glucose of 37.6 %. The wungu leaf extract has the potential to be developed as a source of anti-diabetic agents.